The Potential of Selected Central Asian States to Provide Security in Crises - Pachucki-Włosek, Krystian (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2022)
This article aims to introduce the activities of selected Central Asian countries – having a direct border with Afghanistan, i.e. Turkmenistan, Tajikistan and Uzbekistan – to ensure security after the change of power in Kabul. Familiarisation with the subject matter made it possible to pose the following research questions: 1) Do the selected Central Asian states show predestination to pursue an independent policy towards the Afghan problem? 2) Has the Taliban’s seizure of control of the country been reflected in the strengthening of the position of China, the United States and Russia in the region? 3) ) Has the Taliban’s seizure of control of the country been reflected in the strengthening of the position of China, the United States and Russia in the region?? The collected materials in the form of official government communiqués and press releases provided the key to analyzing the selected actions of state bodies in the situation of increasing threat, tracing the attempts to expand cooperation with subjects of international law understood as states and international organizations. While highlighting the issues of maintaining internal order, it was impossible to omit the issue of the military potential of the state, influencing the security strategy planning process. The main research methods used while creating the article were: synthesis through causal association, analogy, induction and deduction.

Niniejszy artykuł ma na celu przybliżenie działań wybranych państw Azji Centralnej – posiadających bezpośrednią granicę z Afganistanem tzn. Turkmenistan, Tadżykistan i Uzbekistan – dla zapewnienia bezpieczeństwa po zmianie władzy w Kabulu. Zapoznanie się z tematyką umożliwiło postawienie następujących pytań badawczych: 1) Czy wybrane państwa Azji Centralnej wykazują predestynację do prowadzenia niezależnej polityki wobec problemu afgańskiego? 2) Czy przejęcie kontroli nad krajem przez Taliban znalazło swoje odzwierciedlenie w umocnieniu pozycji Chin, Stanów Zjednoczonych i Rosji w regionie? 3) Czy decydenci polityczni Turkmenistanu, Tadżykistanu i Uzbekistanu prowadzą racjonalną politykę wobec talibów? Zebrane materiały w postaci oficjalnych komunikatów rządowych i informacji prasowych zapewniły klucz do przeanalizowania wyselekcjonowanych działań organów państwowych w sytuacji wzrostu zagrożenia, prześledzenia prób poszerzenia współpracy z podmiotami prawa międzynarodowego rozumianymi jako państwa i organizacje międzynarodowe. Naświetlając kwestie utrzymania porządku wewnętrznego, niemożliwe było pominięcie zagadnienia potencjału militarnego państwa, wpływającego na proces planowania strategii bezpieczeństwa. Głównymi metodami badawczymi wykorzystanymi podczas tworzenia artykułu były: synteza poprzez kojarzenie przyczynowe, analogia, indukcja i dedukcja.
Potencjał wybranych państw Azji Środkowej do zapewnienia bezpieczeństwa w sytuacjach kryzysowych
Keywords: Tajikistan; Turkmenistan; Uzbekistan; Afghanistan; the Taliban; security; Tajikistan; Turkmenistan; Uzbekistan; Afghanistan; talibowie; bezpieczeństwo